Si–CNT/rGO Nanoheterostructures as High‐Performance Lithium‐Ion‐Battery Anodes1. Issue 12 (19th October 2015) - Xiao, Lisong; Sehlleier, Yee Hwa; Dobrowolny, Sascha; Orthner, Hans; Mahlendorf, Falko; Heinzel, Angelika; Schulz, Christof; Wiggers, Hartmut
Abstract: A robust and electrochemically stable 3D nanoheterostructure consisting of Si nanoparticles (NPs), carbon nanotubes (CNTs) and reduced graphene oxide (rGO) is developed as an anode material (Si–CNT/rGO) for lithium‐ion batteries (LIBs). It integrates the benefits from its three building blocks of Si NPs, CNTs, and rGO; Si NPs offer high capacity, CNTs act as a mechanical, electrically conductive support to connect Si NPs, and highly electrically conductive and flexible rGO provides a robust matrix with enough void space to accommodate the volume changes of Si NPs upon lithiation/delithiation and to simultaneously assure good electric contact. The composite material shows a high reversible capacity of 1665 mAh g −1 with good capacity retention of 88.6 % over 500 cycles when cycled at 0.5 C, that is, a 0.02 % capacity decay per cycle. The high‐power capability is demonstrated at 10 C (16.2 A g −1 ) where 755 mAh g −1 are delivered, thus indicating promising characteristics of this material for high‐performance LIBs. Abstract : Novel nanoheterostructures : A Si–carbon nanotube (CNT)/reduced graphene oxide (rGO) composite is successfully prepared by using a self‐assembly procedure of a Si–CNT hybrid and graphene oxide, followed by a low‐temperature hydrothermal process. The resulting unique ternary nanoheterostructure integrates the benefits of its building blocks, resulting in a large enhancement in the electrochemical performance.